Intercalation pseudocapacitance in chemically stable Au-α-Fe2O3-Mn3O4 composite nanorod: Towards highly efficient solid-state symmetric supercapacitor device. (20th November 2019) - Rudra, Siddheswar; Chakraborty, Rishika; Maji, Pradip K.; Koley, Sudipta; Nayak, Arpan Kumar; Paul, Debojit; Pradhan, Mukul
Abstract: Pseudocapacitance generally appears due to the surface or near-surface reversible Faradaic reactions. In this regard, 2D layered materials have gained substantial attention as a potential source for driving a myriad of energy storage applications owing to their unique surface-structure relationship. Here, we have demonstrated that a pseudocapacitive mechanism becomes increasingly operative when H + ions are intercalated easily into the enhanced van der Waals gap of layered material α-Fe2 O3 in Au-α-Fe2 O3 -Mn3 O4 nanocomposite. Theoretical studies have shown an enhancement of van der Waals gap which is attributed to the intercalation of Au into the layers of α-Fe2 O3 . Structural and compositional characterizations have been carried out in detailed by different physical methods and are supported by theoretical studies. Electrochemical measurements show excellent specific capacitance of 580 F  g −1 at 1 A  g −1 along with improved capacity retention compared to the mother component α-Fe2 O3 (205 F g −1 at 1 A  g −1 ) in 0.5 M H2 SO4 electrolyte in a potential window of 1.2 V. Further, electrokinetic measurements revealed that total charge stored in the nanocomposite is based on a dominant capacitive mechanism (70% of the total capacitance) along with diffusive mechanism (30% of the total capacitance) at scan rate 5 mV  s −1 whereas, α-Fe2 O3 exhibits 34% capacitive and 66% diffusive at same scan rate. The synthesized composite nanorod as an efficient electrode material in a solid-state symmetric supercapacitor device exhibits excellent energy density of 36.12 Wh kg −1 and power density of 1994 W  kg −1 at 1 A  g −1 and 10 A  g −1, respectively with outstanding stability (89%) up to 2000 successive charge-discharge cycles at 10 A  g −1 . This work may offer a new scope for further development of intercalation pseudocapacitive nanomaterials towards achieving high energy storage supercapacitors. Graphical abstract: Au-α-Fe2 O3 -Mn3 O4 composite nanorod exhibits high energy storage which is ascribed to an enhanced van der Waals gap due to intercalation of Au into the layers of α-Fe2 O3 matrix as supported by experimental and DFT calculations. The expanded interlayer provides for an additional intercalation pseudocapacitance effect to occur on the same time-scale as that of conventional pseudocapacitance.Image 1